Neophyllachora gen nov. (Phyllachorales), three new species of Phyllachora from Poaceae and resurrection of Polystigmataceae (Xylariales) - M. C. Dayarathne (2018)
© Guizhou Academy of Agricultural Sciences. We collected six "tar spot" disease specimens from various hosts and these were subjected to morpho-phylogenetic studies. In this paper, a new genus, Neophyllachora is introduced to accommodate N. cerradensis, N. myrciae, N. myrciariae, N. subcircinans and N. trucantispora, which are related to Phyllachora species but constitutes an independent strongly supported monophyletic clade within Phyllachoraceae of the Phyllachorales. Three novel Phyllachora species; P. chloridis, P. cynodonticola and P. panicicola on Poaceae are also introduced. Phenotypic comparisons and phylogenetic analysis of partial SSU, LSU and ITS sequence data with homologous taxa, confirm the placement of the novel species in Phyllachoraceae. The family Polystigmataceae is re-established to accommodate Polystigma within the order Xylariales. The asexual morph of Polystigma rubrum was re-collected from Russia and is provided as a reference specimen with a description, illustrations and molecular data. Further studies with multiple gene analysis are recommended to provide a natural and stable classification system for members of Phyllachorales.